Visualizing the Bohr effect in hemoglobin: neutron structure of equine cyanomethemoglobin in the R state and comparison with human deoxyhemoglobin in the T state. Issue 7 (5th July 2016) - Dajnowicz, Steven; Seaver, Sean; Hanson, B. Leif; Fisher, S. Zoë; Langan, Paul; Kovalevsky, Andrey Y.; Mueser, Timothy C.
Abstract : The determination of the positions of H/D atoms in equine cyanomethemoglobin by neutron diffraction is described. Abstract : Neutron crystallography provides direct visual evidence of the atomic positions of deuterium‐exchanged H atoms, enabling the accurate determination of the protonation/deuteration state of hydrated biomolecules. Comparison of two neutron structures of hemoglobins, human deoxyhemoglobin (T state) and equine cyanomethemoglobin (R state), offers a direct observation of histidine residues that are likely to contribute to the Bohr effect. Previous studies have shown that the T‐state N‐terminal and C‐terminal salt bridges appear to have a partial instead of a primary overall contribution. Four conserved histidine residues [αHis72(EF1), αHis103(G10), αHis89(FG1), αHis112(G19) and βHis97(FG4)] can become protonated/deuterated from the R to the T state, while two histidine residues [αHis20(B1) and βHis117(G19)] can lose a proton/deuteron. αHis103(G10), located in the α1 :β1 dimer interface, appears to be a Bohr group that undergoes structural changes: in the R state it is singly protonated/deuterated and hydrogen‐bonded through a water network to βAsn108(G10) and in the T state it is doubly protonated/deuterated with the network uncoupled. The very long‐term H/D exchange of the amide protons identifies regions that are accessible to exchange as well as regions that are impermeable to exchange. The liganded relaxed state (R state) has comparable levels of exchange (17.1% non‐exchanged) compared with the deoxy tense state (T state; 11.8% non‐exchanged). Interestingly, the regions of non‐exchanged protons shift from the tetramer interfaces in the T‐state interface (α1 :β2 and α2 :β1 ) to the cores of the individual monomers and to the dimer interfaces (α1 :β1 and α2 :β2 ) in the R state. The comparison of regions of stability in the two states allows a visualization of the conservation of fold energy necessary for ligand binding and release.